HUBUNGAN BEBAN KERJA DENGAN STRES KERJA PERAWAT DI KLINIK TERATAI MEDICAL CENTRE - Efrata Sembiring; Viktor Edward Marbun; Rian Fedriko Ginting; Evalina Manurung (Jurnal Penelitian Kesmasy, 2021)
This study aims to determine the relationship between workload and work stress of nurses at the Teratai Medical Center Clinic. Work load is the ability possessed by individuals to complete a work demand that must be completed at a certain time. Job stress is a reaction to a person's inability to adapt and cope with stressors due to changes experienced. The research design used in this study was an analytical survey with a cross sectional approach. The population in this study were 38 respondents with a sample of 38 respondents with the sampling technique using total sampling. Data collection was carried out by using a workload and work stress questionnaire. Based on the results of the data analysis conducted, it was found that there was a significant relationship between workload and work stress. This can be seen from the results of statistical tests carried out with the Chi-Square test, namely the p value (sig) 0.026 <a = 0.05, this means that the proposed hypothesis has a relationship between workload and work stress. There is a relationship between workload and work stress on nurses at the Teratai Medical Center Clinic.